IMPLEMENTEASI KEBIJAKAN BARANG MILIK DAERAH PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) PROVINSI BANTEN - Toni Anwar Mahmud; Rina Dewiyanti; Syifa Rachmania Komara (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2024)
ABSTRACT Regional Property must be managed properly and correctly by paying attention to functional principles, legal certainty, transparency, efficiency, accountability and certainty of value. The Banten Provincial Government, to be able to implement the provisions of Government Regulation Number 27 of 2014 and Article 511 paragraph 1 of the Minister of Home Affairs Regulation Number 19 of 2016 concerning Guidelines for Management of Regional Property, has issued Banten Province Regional Regulation Number 1 of 2019 concerning the management of regional property. However, in implementation there are still several obstacles faced by Banten Province, especially the Regional Financial and Asset Management Agency (BPKAD) in managing regional property in several cycles. Based on this and considering the importance of Regional Property Management, the regional government of Banten Province together with BPKAD is expected to be able to find efforts and implement appropriate and reliable strategies in managing regional property, especially in planning activities and budgeting needs for regional property.